Donning and doffing. - Antonio Rodríguez-Fernández (317652) (2025)
(a) Time needed and LOA required for donning both the KAFOs and the ABLE exoskeleton for all the sessions of the study. (b) Time needed and LOA required for doffing both the KAFOs and the ABLE exoskeleton for all the sessions of the study. Dots indicate the participants’ real time. Solid lines show the general model of the metrics and the faded surfaces indicate the 95% CI of the general models. Stars (*) indicate statistically significant differences (p < 0.05).